An integrated strategy for improving the desalination performances of activated carbon-based capacitive deionization systems. (10th April 2019) - Chen, Yi-Jing; Liu, Ching-Fang; Hsu, Chun-Chia; Hu, Chi-Chang
Abstract: In capacitive deionization (CDI) systems, more Faradaic reactions generally occur at a higher cell voltage, resulting in the poor ion-removal efficiency and high energy consumption, but a low cell voltage may lead to a low deionization capacity. In this study, an integrated strategy, consisting of (1) selecting the acceptable charge/discharge time ratio, (2) finding the potential windows of both positive and negative electrodes, and (3) using the charge-balanced method for determining the optimal mass ratio between the positive and negative electrodes (denoted as (m + )/(m − )), is proposed to find the optimal cell voltage of a CDI system with a high desalination efficiency and low energy consumption. According to this strategy, two newly designed cells using two types of activated carbon (AC) show excellent CDI performances; cell 1 with AC = ACS679, (m + )/(m − ) = 1:1.4, and cell voltage = 1.4 V: salt adsorption capacity of 12 mg g −1, charge efficiency of 62%, and energy consumption of 109 kJ mol −1 and cell 2 with AC = ACS25, (m + )/(m − ) = 1:1, and cell voltage = 1.2 V: salt adsorption capacity of 13 mg g −1, charge efficiency of 81%, and energy consumption of 72 kJ mol −1 although the potential window of water decomposition for such AC-coated electrodes in 8 mM NaCl is about 2 V. This universal strategy is applicable to all CDI systems utilizing various electrode materials. Graphical abstract: Image 1 Highlights: We demonstrate a universal strategy for constructing the AC//AC cell with high CDI performances. The same charge/discharge time ratio with high reversibility on both electrodes is the key. Influences of two-electrode mass ratio on the desalination performances are studied. The pH change is affected by the Faradaic reactions from the potential windows of electrodes.